Adenosine A2A receptor, a potential valuable target for controlling reoxygenated DCs-triggered inflammation. Issue 2 (February 2015) - Liu, Chunmei; Shang, Qianwen; Bai, Yang; Guo, Chun; Zhu, Faliang; Zhang, Lining; Wang, Qun
Highlights Reoxygenated DCs, predominantly expressed high levels of adenosine receptor A2AR. Activation of A2AR could inhibit the maturation and activation of reoxygenated DCs. Proposing A2AR as a target for controlling reoxygenated DCs-triggered inflammation.